2013
DOI: 10.1159/000354452
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of MiR-30c Promotes the Invasion of Non-Small Cell Lung Cancer by Targeting MTA1

Abstract: Background: The connection between microRNA expression and lung cancer development has been identified in recent literature. However, the mechanism of microRNA has been poorly elucidated in non-small-cell lung cancer (NSCLC). Methods and Results: Comparing with adjacent tissues (n=75), miR-30c has a lower expression in lung cancer specimens (n=75). The knockdown of miR-30c enhanced the invasion of A549 cells; meanwhile, the overexpression of miR-30c could reverse the effect of the knockdown of miR-30c in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…This suggests that miRNAs are central regulators of cancer. Xia et al [27] recently Figure 3. miR-125a-3p suppresses the proliferation of NSCLC cells by inhibiting MTA1 (A) MTT assay, (B) colony formation assay, and (C) EdU assay were performed in SPC-A-1 and 95D cells co-transfected with miR-125a-3p or miR-NC and si-MTA1 or scrambled siRNA.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that miRNAs are central regulators of cancer. Xia et al [27] recently Figure 3. miR-125a-3p suppresses the proliferation of NSCLC cells by inhibiting MTA1 (A) MTT assay, (B) colony formation assay, and (C) EdU assay were performed in SPC-A-1 and 95D cells co-transfected with miR-125a-3p or miR-NC and si-MTA1 or scrambled siRNA.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Gu and his co-workers verified that miR-150 induced cell proliferation inhabitation and apoptosis in NSCLC by targeting BAK1 [19]. Meanwhile, our previous work has also confirmed that miR-204 and miR-30c function as regulators in the progression of NSCLC by targeting specific genes [15,16]. Recently, miR-452 was regarded as tumor suppressor in glioma [7], prostate [20] and breast malignancies [8], which was supported by our findings that miR-452 expression was significantly reduced in tumor comparing with corresponding adjacent tissues and was negatively correlated with the tumor stage and lymph nodes metastases.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous studies have illustrated that invasion and metastasis are key factors influencing the rate of long-term survival of NSCLC [15,16]. Even diagnosed at early stage and surgically resected successfully, a considerable number of NSCLC patients will suffer from metastasis or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs bind target mRNAs at complementary sites in their 3'-untranslated regions (3'-UTRs), thereby suppressing the expression of the target gene at the posttranscriptional level [19][20][21]. Through this mechanism, miRNAs regulate a wide range of biological processes, including cell proliferation and differentiation [22], migration, apoptosis, development, and metabolism [23][24][25]. For example, miR-545 suppress cell proliferation by targeting Cyclin D1 and CDK4 in lung cancer cells [26].…”
Section: Down-regulation Of Adam17 By Sirna Reversed the Effect Of MImentioning
confidence: 99%